Surface design of nanocarriers: Key to more efficient oral drug delivery systems - Spleis, Helen; Sandmeier, Matthias; Claus, Victor; Bernkop-Schnürch, Andreas (Advances in colloid and interface science, 2023)
As nanocarriers (NCs) can improve the solubility of drugs, prevent their degradation by gastrointestinal (GI) enzymes and promote their transport across the mucus gel layer and absorption membrane, the oral bioavailability of these drugs can be substantially enhanced. All these properties of NCs including self-emulsifying drug delivery systems (SEDDS), solid lipid nanoparticles (SLNs), nanostructured lipid carriers (NLCs), liposomes, polymeric nanoparticles, inorganic nanoparticles and polymeric micelles depend mainly on their surface chemistry. In particular, interaction with food, digestive enzymes, bile salts and electrolytes, diffusion behaviour across the mucus gel layer and fate on the absorption membrane are determined by their surface. Bioinert surfaces limiting interactions with gastrointestinal fluid and content as well as with mucus, adhesive surfaces providing an intimate contact with the GI mucosa and absorption enhancing surfaces can be designed. Furthermore, charge converting surfaces shifting their zeta potential from negative to positive directly at the absorption membrane and surfaces providing a targeted drug release are advantageous. In addition to these passive surfaces, even active surfaces cleaving mucus glycoproteins on their way through the mucus gel layer can be created. Within this review, we provide an overview on these different surfaces and discuss their impact on the performance of NCs in the GI tract. [Display omitted] •The fate of oral NCs (SEDDS, SLN, NLC, liposomes, polymeric/inorganic nanoparticles) depends on their surface chemistry.•Bioinert surfaces limit interactions with GI content and mucus guaranteeing that NCs can reach the absorption membrane.•Adhesive surfaces provide an intimate contact with the GI mucosa and a prolonged residence time.•Absorption enhancing surfaces guarantee an improved drug permeation of the epithelial cell layer.•Surfaces that shift their zeta potential from negative to positive at the absorption membrane improve cellular uptake.